Deformità fisica e identità della persona tra medioevo ed età moderna (Centro di Studi sulla Civiltà del Tardo Medioevo San Miniato, 2015)
In recent decades, European historiography has actively dealt with the history of the body, thus giving depth and awareness to powerful stimuli coming from the dominant culture in the affluent society. Therefore, object of research has been not only the 'beautiful' body, but also the body of the common man, mutilated, deformed and imperfect. Through surveys in legal-regulatory, registry, iconographic, literary sources and in medical and physiognomic treatises and thanks to the participation of some of the major international specialists in the field, the volume intends to investigate these issues especially in the geographical, cultural and documentary context of Italy in the late Middle Ages and the early modern age, which has so far remained on the margins of this line of studies.